Dynamic Model for Food Security to Realize Food Sovereignty: Case Study in Bantul Regency of Yogyakarta Special Region - Ayub Ayub; Bambang Pramudya Noorachmat; Muhammad Yanuar Jarwadi Purwanto (School of Postgraduate Studies, Diponegoro Univer, 2023)
The increased populism should be offset by increased food production; thus, the region's food security can be maintained. Food security will not be resolved if it does not solve the root of the problem, namely the farmers' deterioration and the agricultural land conversion. The primary purpose of this study is to design a dynamic model of sustainable food farming—the methods used in achieving an approach with a dynamic system. Needs analysis, problem formulation, system identification, system modeling, model validation, and implementation are the stages in problem-solving with the systems approach method. The Powersim Studio software analyzes the system and views model behavior. Based on the predicted results, in 2021, Bantul Regency experienced a deficit rice of 1,925 tons without control efforts. A pessimistic scenario with a control policy of 50% of the rice field function transfer rate caused the rice balance sheet to be a deficit of 1,001 tons. Optimistic scenario, control of paddy field conversion 50% of the transfer rate and food diversification obtained rice balance with a surplus of 5,460.24 tons by 2030.